Cold Weather Construction Materials. Part 2. Regulated-Set Cement for Cold Weather Concreting. Field Validation of Laboratory Results. - Houston,Billy J; Hoff,George C (1981)
The U.S. Army carries on construction projects in localities such as Alaska, the northern tier of the United States, northern Europe, and the Arctic where the concrete placing system is shortened by the cold climate. At ambient temperatures below 50 F, concreting operations become more expensive since Corps of Engineers specifications require freshly mixed and placed concrete to be protected from low ambient temperatures. The overall military construction and maintenance in cold regions program was initiated to locate and evaluate existing and new cementing materials that would allow concrete to be placed at ambient temperatures as low as 15 F. A relatively newly developed cement called 'regulated-set' cement, which is a fast setting, rapid strength gain cement, appeared to have promise and was selected for a detailed study. (Author) See also Part 1, AD-A021 658.